RESPONSE OF ANTI-CANINE PARVOIRUS IMUNOGLOBULIN YOLK ADMINISTRATION ON PUPPY RAISED IN CANINE PARVOVIRUS CONTAMINATED AREA - Leonard, Angel Novelyn; Suartini, I Gusti Ayu Agung; Utama, Iwan Harjono (Buletin Veteriner Udayana, 2022)
Canine parvovirus is an infectious virus that mostly affects puppies. So far, prevention and therapy of CPV infection in dogs has been limited to providing supportive therapy. Prevention of CPV infection is very important, especially in puppies whose parents have not been vaccinated. The purpose of this study was to determine the response of puppies given egg yolk containing IgY anti-CPV dose of 3 ml/head/day and kept in a contaminated location. One possible modality is the administration of passive antibodies in the form of egg yolk containing antibodies (Immunoglobulins Yolk/IgY) that are specific for CPV. This study used 5 puppies aged 2 months divided into two groups, treatment group (P) which was given 3 ml/head/day of anti-CPV IgY with a dose of 2 14 HI units and 2 control groups. For 14 days the dogs were observed for clinical symptoms, serum was tested by the HI method to determine the presence of antibodies to CPV and leukocyte profile was detected by blood smear and examined manually under a microscope. The results showed that the maternal antibody titer was below the protective titer. Provision of egg yolk containing anti-CPV IgY was able to maintain protective antibody titers up to day 12 of treatment. Of the 3 puppies who were given egg yolks containing IgY, two of them died because they were positive for CPV. One recovered after Intravenous IgY anti-CPV therapy. It was concluded that the administration of anti-CPV IgY egg yolk at a dose of 3 ml/puppy/day was not protective enough to protect puppies from CPV infection. Effectivity can be increased by increasing the dose given.